Design and analysis of 3D-printed PLA scaffolds: Enhancing mechanical properties - Aquib Rahman; Kazi Farhan Tanvir; Halima Khatun Jui; Md. Tanvir Ahmed; Shah Md Ashiquzzaman Nipu; Shaikh Bin Hussain (Results in Engineering, 2025)
3D printing has enabled researchers to create scaffolds that possess high mechanical compatibility. So far, printed scaffold structures have primarily focused on simple designs, leading to a limited understanding of complex structures. This study aims to create scaffolds by easily sourced 3D printing system (FDM) and material, Polylactic Acid (PLA), to improve surface area, porosity, and reduce weight. The study presents two innovative scaffold designs, Hybrid Dome Face Centered Porous Structure (HDFCPS) and Reinforced Dome-Arch Porous Structure (RDAPS) inspired by literature and compares their mechanical performance with three traditional scaffold designs under controlled conditions. Finite element analysis and experimental tests are used to determine the mechanical properties of the 3D-printed scaffolds. Key findings of the study include superior stress distribution, reduced weight and better surface area for both designs. The Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS) was implemented to determine the optimum design. Maximum stress, total deformation, surface area and weight were used as the criteria for TOPSIS. While both new structures showcased improvements, HDFCPS was selected as the best structure according to TOPSIS analysis, with the highest load-bearing capacity (35.3 % higher compared to RDAPS). Furthermore, the study results showed a high porosity percentage (≥80 %) for all the structures indicating potential capabilities for early state vascularization and cell migration. Such characteristics closely align with the desired increased attributes for a bone scaffold in promoting higher bone regeneration. This study provides notable contributions by providing easily manufacturable, cost-efficient new scaffold designs.